Adjusting Dairy Housing in Hot Climates to Meet Animal Welfare Requirements - Samer, M. (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Small dairy farms in hot climates are encountering several problems caused by the design flaws of the implemented housing designs. Consequently, heat stress increase and milk yield dramatically decreases, which leads to economic deficiency of the farm. One key issue is to develop simple means to rectify the design flaws with minimum costs. In order to develop feasible means, design flaws were detected on-site in 14 small dairy farms in Egypt to exemplify the flaws of housing designs in arid and semi-arid zones. A package of interconnected solutions is suggested to rectify the design flaws. Subsequently, the maximum temperature, dry-bulb temperature, black-globe temperature, dew point, relative humidity, shaded area, and air velocity were measured inside the rectified vs. non-rectified cowsheds and compared after conducting the statistical analysis. On the other hand, the Temperature-Humidity Index (THI) and Black Globe Humidity Index (BGHI) were calculated to find out the level of heat stress affecting the dairy cows. Furthermore, the milk yield, respiration rate, skin temperature, feed intake were recorded and compared. Moreover, the costs of the developed means were calculated and a feasibility study was carried out. The results show that the developed means are effective and feasible, where the heat stress decreased (THI decreased from 94.6 to 83.7; dry-bulb temperature decreased from 42.7 to 33.6 oC) and the average milk production increased from 18 to 26 kg/day.cow. Consequently, the costs were minimized and the revenues were maximized, which achieve economic efficiency for the farm where the profit increased by about 427 $/cow.year. -------------------------------------------------------------------------------------------------------- Assistant Professor, Agricultural Engineering Department, Faculty of Agriculture, Cairo University, Gammaa Street, 12613 Giza, Egypt * Corresponding Author, Email: samer@cu.edu.eg Please Cite This Article As: M. Samer. 2010. Adjusting Dairy Housing in Hot Climates to Meet Animal Welfare Requirements. J. Exp. Sci. 1(3): 14-18.